PROSPECTS FOR CYTOPROTECTORS USE IN THE ELDERLY PATIENTS THROUGH THE EXAMPLE OF CALCIFIED AORTIC STENOSIS AND ISCHEMIC HEART DISEASE - N. Yu. Karpova; M. A. Rashid; N. A. Shostak; I. V. Pogonchenkova; T. V. Kazakova (Рациональная фармакотерапия в кардиологии)
Issues of pathogenesis of the calcified aortic stenosis and ischemic heart disease in the elderly are considered. The relevance of early detection of angina, syncope, and dyspnea in view of their non-specific and subclinical course for early detection of heart disease is specified. Current scientific views on the myocardial bioenergy and its role in the genesis of chronic heart failure are presented. Particular attention is paid to the place of cytoprotectors, especially trimetazidine, in the management of patients with cardiac N.Yu. Karpova1diseases.